Art spaces and urban policy: The integration of art spaces in urban gentrification processes - Bolonaki, Styliani (The Greek Review of Social Research, 2025)
The article focuses on the new art spaces in Athens, which, under the umbrella term of creative initiatives have evolved into factors of the Athenian urban renaissance, employing creativity as a driving force to the socio-economic development of the Athenian districts. The text elaborates on the characteristics of these spaces, analyzing their genealogy and dynamic integration into the city's production, focusing on the examples of European cities and giving particular emphasis to the model applied in Paris today. The article draws from two epistemological fields: urban studies and the sociology of art, wishing to offer a new perspective on communication channels between art practices and urban politics.